Karakteristik Pondok Pesantren Al-Ihsan dalam Tinjauan Analisis SWOT - Rida Nurfarida; Muhamad Tisna Nugraha; Andewi Suhartini; Nurwadjah Ahmad (STKIP PGRI SITUBONDO, 2022)
Pesantren (Islamic boarding schools) is one of the oldest Islamic educational institutions in Indonesia. Pesantren can produce the next generation of the nation who have the capability to carry the message of da’wah to various regions based on the sources of Islamic teachings, namely the Qur’an and Hadiths. This is as carried out by Pondok Pesantren Al-Ihsan (English: Al-Ihsan Islamic Boarding School) which is located at Jalan Cibiru Hilir No. 23, Cibiru Hilir Village, Cileunyi, Bandung Regency. This study aimed at reviewing the characteristics of Al-Ihsan Islamic Boarding School through a SWOT analysis (strengths, weaknesses, opportunities, and threats). In this study, the researcher applied a qualitative approach with descriptive analysis. Furthermore, the data were collected through observation, interviews, and documentation. Results indicate that Al-Ihsan Islamic Boarding School has at least six characteristics that distinguish it from other Islamic boarding schools, namely (1) integrality, (2) moderateness, (3) inclusivity, (4) holistic feature, (5) simplicity, and (6) Islam amaliy. These six characteristics are the strengths of Al-Ihsan Islamic Boarding School when compared to other Islamic boarding schools around it. Meanwhile, its weaknesses are technology advancements and the swift current of globalization. Therefore, the six characteristics possessed by Al-Ihsan Islamic Boarding School often face limited quality of human resources and problems related to the adjustment to the management of digital-based educational and institutional activities. Furthermore, the opportunities possessed by Al-Ihsan Islamic Boarding School are found in its moderateness and inclusivity characteristics so that this Islamic boarding school tends to be able to adapt to the times. The threats faced with its moderateness and inclusivity characteristics are the possibility of an identity crisis that may undermine the meaning and spirit of Islamic boarding school education systems.